Kajian terhadap Sarana Duduk Publik Kampus dengan Pendekatan Perilaku dan Aktivitas Warga Kampus (Studi Kasus pada Kampus Institut Teknologi Bandung Ganesha) - Arianti Ayu Puspita; Dudy Wiyancoko; Dona Saphiranti (Journal of Visual Art and Design, 2013)
This research is motivated by a number of outdoor public furniture, which is not functional, not in place and even unused. The expected result is the discovery of a tendency of design criteria to sit to meet the needs of students. "Sunken Court" was the first major project from seven planning areas  and  a case method in this paper. Three theories of human behavior from Elizabeth D. Hutchison, Christopher Alexander and Edward T. Hall are used as an approximation method to observe students activities at seven case areas in Institut Teknologi Bandung. Those theories are used in observation step according to environmental dimensions, time dimensions and personal dimensions, and the results are 15 design principles references about seating facilities from human behavior aspects and produce the tendency of seating facilities design. The outputs of observation from seven case areas are arranged in appendix so it can be used for the next research.